Determination of the world stock indices' co-movements by association rule mining - Burcu Kartal; Mehmet Fatih Sert; Melih Kutlu (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - This study aims to provide preliminary information to the investor by determining which indices co-movement, with the data mining method. Design/methodology/approach - In this context, data sets containing daily opening and closing prices between 2001 and 2019 have been created for 11 stock market indexes in the world. The association rule algorithm, one of the data mining techniques, is used in the analysis of the data. Findings - It is observed that the US stock market indices take part in the highest confidence levels between association rules. The XU100 stock index co-movement with both the European stock market indices and the US stock indices. In addition, the Hang Seng Index (HSI) (Hong Kong) takes part in the association rules of all stock market indices. Originality/value -The important issue for data sets is that the opening/closing values of the same day or the previous day are taken into account according to the open or closed status of other stock market indices by taking the opening time of the stock exchange index to be created. Therefore, data sets are arranged for each stock market index, separately. As a result of this data set arranging process, it is possible to find out comovements of the stock market indexes. It is proof that the world stock indices have co-movement, and this continues as a cycle.
Keywords: C6; C8; G15; 330; Data mining; Association rules; Stock market index; Global financial markets